Mapping the spread of dengue fever with geographic information system in Magelang City in 2020-2024 - Nurul 'Ain, Adinda Dwi; Pratiwi, Rita Dian (International Journal of Health Science and Technology, 2025)
Dengue Hemorrhagic Fever (DHF) cases are rising in Magelang City, yet current reporting lacks distribution maps, hindering identification of high-risk areas. This quantitative descriptive study, therefore, aimed to analyze DHF distribution in Magelang City (2020-2024) using a Geographic Information System (GIS) and identify dominant influencing factors. Employing a cross-sectional design, secondary data on DHF cases, rainfall, temperature, humidity, population density, and Larvae Free Rate (LFR) were collected. Data analysis involved spatial methods with QGIS and statistical methods (Geographically Weighted Regression/GWR) via RStudio. Results showed climate factors (rainfall, temperature, humidity) and population density exhibited homogeneous patterns, not significantly explaining DHF case variations. While LFR was generally high (>90%), a positive anomaly in 2023 saw high LFR followed by increased cases. The DHF distribution pattern fluctuated, peaking in 2022. In conclusion, none of the studied factors (climate, population density, LFR) were identified as significant dominant influences on DHF distribution. LFR anomalies suggest program interventions responding to high caseloads. DHF distribution is likely due to complex interactions of other unstudied factors (e.g., PSN effectiveness, behavior, sanitation, community knowledge). GIS remains valuable for data driven DHF prevention planning.